An Ultra‐High Fluorescence Enhancement and High Throughput Assay for Revealing Expression and Internalization of Chemokine Receptor CXCR4. Issue 17 (9th March 2016) - He, Hua; Wang, Xiaojuan; Cheng, Tiantian; Xia, Yongqing; Lao, Jun; Ge, Baosheng; Ren, Hao; Khan, Naseer Ullah; Huang, Fang
Abstract: Revealing chemokine receptor CXCR4 expression, distribution, and internalization levels in different cancers helps to evaluate cancer progression or prognosis and to set personalized treatment strategy. We here describe a sensitive and high‐throughput immunoassay for determining CXCR4 expression and distribution in cancer cells. The assay is accessible to a wide range of users in an ordinary lab only by dip‐coating poly(styrene‐co‐ N ‐isopropylacrylamide) spheres on the glass substrate. The self‐ assembled spheres form three‐dimensional photonic colloidal crystals which enhance the fluorescence of CF647 and Alexa Fluor 647 by a factor of up to 1000. CXCR4 in cells is detected by using the sandwich immunoassay, where the primary antibody recognizes CXCR4 and the secondary antibody is labeled with CF647. With the newly established assay, we quantified the total expression of CXCR4, its distribution on the cell membrane and cytoplasm, and revealed their internalization level upon SDF‐1α activation in various cancer cells, even for those with extremely low expression level. Abstract : A microarray immunoassay with ultra‐high fluorescence enhancement and high throughput capacity has been developed. By using this assay, low‐abundance CXCR4 surface expression was detected and differentiated and their internalization levels in different cancer cells was revealed.